1971
DOI: 10.1021/ac60305a018
|View full text |Cite
|
Sign up to set email alerts
|

Rotated mercury cell for controlled potential coulometry. Elimination of background current by digital normalization

Abstract: A cell which is rotated at high speeds and contains a thin-layer, mercury, working electrode has been developed for controlled potential coulometric determinations. The cell, which is the first successful departure from stirred mercury pool types, has several advantageous features. Constant mercury geometry Briefly mentioned in a previous paper (J), but detailed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Anson (10) determined that adsorbed Brcatalyzed the oxidation of the EDTA-Co(I1) anion. Hubbard and co-workers (11)(12)(13)(14) 16) reported the electrocatalysis of the oxidation of ascorbic acid by adsorbed I a t a Pt electrode. Recently, Johnson and Resnick (17) reported that the reduction of Fe(II1) in HC104 solutions is irreversible in the absence of traces of dissolved halides but is dramatically catalyzed by addition of halide salts, including I-, a t micromolar levels.…”
Section: Resultsmentioning
confidence: 99%
“…Anson (10) determined that adsorbed Brcatalyzed the oxidation of the EDTA-Co(I1) anion. Hubbard and co-workers (11)(12)(13)(14) 16) reported the electrocatalysis of the oxidation of ascorbic acid by adsorbed I a t a Pt electrode. Recently, Johnson and Resnick (17) reported that the reduction of Fe(II1) in HC104 solutions is irreversible in the absence of traces of dissolved halides but is dramatically catalyzed by addition of halide salts, including I-, a t micromolar levels.…”
Section: Resultsmentioning
confidence: 99%